Rancang Bangun Sistem Informasi Penilaian Pencapaian Materi dan Absensi Murid di Taman Pendidikan Al-Quran (TPA) DPD Lembaga Dakwah Islam Indonesia Kabupaten Manokwari menggunakan Metode Prototype - Afifah Ummi Sholihah; Christian Dwi Suhendra; Pawit Rianto (Faculty of Computer Science, University of Jember, 2021)
The Regional Representative Council of Indonesia Institute of Islamic Dakwah of Manokwari Regency has four departments from Al-Quran Education School which are required to report the attendance and achievements of students each month in their respective departments. This report will be presented to the parents and to the Head of the school for evaluation. Both of these assessments are still carried out manually so it is inefficient because the data will be easily lost or scattered. With these problems, the author did some researches to carry out the Design and Development of Information System for Assessment of Material Achievement and Student Attendance at Al-Quran Education School - Regional Representative Council of Indonesia Institute of Islamic Dakwah in Manokwari Regency. This research was conducted by creating an assessment input information system and responsive web-based data recap, using the Laravel framework, MySQL database and the research method used was the Prototype Method. At the final stage of this research is testing the system with the Black Box Method. The final result of this research is the formation of the Information System for Assessment of Material Achievement and Student Attendance for the Al-Quran Education School - Regional Representative Council of Indonesia Institute of Islamic Dakwah in Manokwari Regency. The test results show that the Prototype Method can be used in building the information system in question.